(untitled) (Journal of Dhaka Medical College, 2018)
Background: Vitamin D deficiency (VDD) is widespread, yet it is the most underdiagnosed and undertreated nutritional deficiency in the world. The prevalence of VDD is estimated to affect over 1 billion people worldwide. The present study was conducted to estimate the prevalence of VDD among adults aged 18–89 years visiting the outpatient department in a clinic/chamber. Objective: To assess the status of vitamin D deficiency (VDD) among the adult population in Bangladesh. Methods: A cross sectional study was conducted among 189 adults in the year 2017 including both males and females aged 18–89 years in outpatient department of a clinic/chamber. Venous blood sample was collected for the measurement of Vitamin D (25 hydroxyvitamin D). Results: This study included a total of 189 adults (29 males and 160 females) aged between 18 and 89 years. Majority of the patients were vitamin D deficient, 67.2% and 20.6% were suffering from vitamin D insufficiency. Maximum males and females are deficient, 69% and 66.9% respectively where as a very small percentage has sufficient level of vitamin D. Conclusions: Vitamin D deficiency (VDD) is alarmingly high. Screening services should be implemented while researchers focus on strategies to lessen the incidence and morbidity associated with these conditions. J Dhaka Medical College, Vol. 27, No.1, April, 2018, Page 94-97